Accumulation of Lawsuits and Applications in the Case of Revocation of Custody and Determination of Guardianship of Adult Children: Study of Decision No. 376/Pdt.G/2021/PA. Klk - Nastiya, Tri; Harahap, Mhd Yadi (PALAR (Pakuan Law review), 2025)
Abstract  Regulations in Indonesia state that a child under the age of 18 is under the authority of their parents, who are obligated to care for, educate, and meet the child’s needs, as stipulated in Article 47 paragraph (1) of Law No. 1 of 1974 on Marriage. Based on this provision, this study examines the legal issues in Decision Number 376/Pdt.G/2021/PA.Klk of the Religious Court of Kolaka, which granted a claim for the revocation of parental authority and simultaneously appointed a guardian for an individual who was already 20 years and 4 months old.The research addresses two main issues: the inappropriateness of the legal subject who, according to positive law, is already an adult; and a procedural defect in the form of the combination of two different types of cases in a single proceeding—namely, a contentious claim (contentiosa) and a non-contentious petition (voluntair).This study adopts a normative legal approach with two methods of analysis: statutory approach and case study approach. The sources of data include primary, secondary, and tertiary legal materials. The analysis reveals that the court’s decision is inconsistent with the principles of civil procedural law, which clearly distinguishes between claims and petitions. Furthermore, the appointment of a guardian for a legal subject who has reached adulthood without proving legal incapacity contradicts the provisions of Islamic law, the Indonesian Civil Code, and the Compilation of Islamic Law.Thus, the ruling contains both formal and material errors. This study highlights the importance of consistent application of the legal age of adulthood and formal clarity in the submission of cases in religious courts. Keywords: Parental Authority, Guardianship, Civil Procedural Law, Adult Child, Religious Court